Troubling images : visual culture and the politics of Afrikaner nationalism - Freschi, Federico; Schmahmann, Brenda, 1960-; Van Robbroeck, Lize (Wits University Press, 2020)
"Troubling Images explores how art and visual culture helped to secure hegemonic claims to the nation-state via the construction of a unified Afrikaner imaginary."--Publisher's description